(untitled) (Heritage, 2024)
The neoliberal interpretation in the terminological sense arose after the mention of the German economist Alexander Ristov in a meeting that took place in 1938 in Paris as part of a gathering of European intellectuals of that era. However, the rapid rise of this concept happened after the establishment of the power of Margaret Thatcher in Britain, essentially after 1979, and then the coming to power of Ronald Reagan in 1981 in the USA. The application of the thesis of neo-liberalism is linked to the formation of the economic policy that was mainly implemented by Great Britain and the USA. With the formation and adoption of Mont Pelerin’s ideas, an international society of economic theorists was created, which evidently had an impact on economic theory and the formation of attitudes related to the liberal concept of influence on other countries. Neo-liberalism at the time of its emergence represented basically the ideas of the trans-national bourgeoisie. However, the application of this concept has a drawback, which is manifested in the existence of insufficient connection with social structures within national societies.